The Relationship Between Parental Knowledge and Children’s Behavior in Disposing of Garbage - Noviana Sari; Dadang Kusbiantoro; Sylvi Harmiardillah; Zusnia Ajeng Dewi Ningrum (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Parents' knowledge of children's littering behavior is an important thing that needs to be considered by every parent. That needs to be considered by every parent, because it can help children's behavior towards a positive direction, especially in disposing of garbage. The purpose of this study was to determine the relationship between the level of knowledge parents with children's behavior of throwing garbage. This research design uses correlation analytics with crosssectional approach. The sample of this study was 63 respondents using random sampling technique. The independent variable in this study is parental knowledge, while the dependent variable in this study is children's littering behavior. This study is the behavior of children to dispose of garbage. Data were collected using a questionnaire of parental knowledge knowledge questionnaire and observation of children's waste disposal behavior. Data were analyzed using the chi-square test with a significance level of p<0.05. p<0.05. The results showed that almost half (46.0%) of parents' knowledge was good, and more than half (66.7%) of children's behavior was good. More than half (66.7%) of children's behavior to dispose of garbage in its place with their own awareness. The results of data analysis the results of data analysis obtained a value of p = 0.000 <0.05, meaning that there is a relationship between parental knowledge and children's behavior. Behavior to dispose of garbage. The results of this study are expected to be used as information about development in the community in parental knowledge with children's behavior of throwing garbage.